Temporal and Evolutionary Analysis of Urban Linear Water Erosion in a Hillslope Located in the Source Region of Córrego da Grama - Oliveira, Ana Laura Pascucci de; Francisco, Matheus Ribas; Furegatti, Simone Andrea (Technical and Scientific Journal Green Cities, 2022)
Urban erosion processes are caused by a combination of natural factors, such as relief, soil type and management, among others, and can be aggravated by human action over time. The objective of the work presented here was to carry out a case study of water erosion on a hillslope located in the source region of Córrego da Grama, in the Bauru/SP peripheral region, to analyze the temporal evolution and the main factors of influence on the emergence of visible features in satellite images, through systematization of the characteristics of each erosion. The organization of the information allowed a better understanding of the processes, their origins and the reasons that contribute to their persistence, correlating them with the environment and forming an overview of the events that happen on the hillslope.